New Approach: Design of Compact Baugh-Wooley Multiplier Using Reversible Logic - V. Rajmohan; O. Uma Maheswari (New Insights into Physical Science Vol. 12, 2021)
In today’s digital era, developing digital circuits is bounded by the research towards investigating various nano devices. This paper provides the design of compact Baugh-Wooley multiplier using reversible logic. Even though various researches have been done for designing reversible multiplier, this work is the first in the literature to use Baugh-Wooley algorithm using reversible logic. In this work, a new 5 × 5 reversible multiplier cell is proposed which will be useful in designing Baugh-Wooley multiplier. The proposed single multiplier cell is able to perform addition of a 1 × 1 product with the sum and carry from the previous cell. This reversible multiplier cell is useful in building up regularity in the array multipliers. The Toffoli gate synthesis of the proposed reversible multiplier cell is also given. It is comprehended that the number of gates, the constant inputs and garbage outputs values are fewer in number in the proposed design compared to the existing approaches. The design can be enhanced to construct n × n reversible Baugh-Wooley multiplier circuit.